Profilistic Study of Bioactivities of Extracts of Gongronema latifolium Incorporated with Alum on some Clinical Bacteria (International Current Pharmaceutical Journal, 2018)
Profilistic study of bioactivities of aqueous, ethanolic and methanolic leaf extracts of Gongronema latifolium in combination with potassium aluminium sulphate (Alum) against some clinical bacterial pathogens were investigated by disc diffusion (DD) and Agar well diffusion (AWD) methods respectively. The leaf extracts at concentrations of 0.1-0.3g were reconstituted in sterile distilled water as well as 1.0-3.0g of alum prior to application. In-vitro bioactivity of various concentrations of the extracts and in combination with alum were evaluated by measuring diameter of inhibition zones (DIZs) respectively. Methanolic leaf extract (MLE) had the largest mean DIZs of 14.5±0.5 and 11.5±0.0mm on Escherichia coli and Salmonella typhi, with enhanced bioactivity of 19.5±0.7 and 17.5±0.7mm with alum against Bacillus subtilis, Sal. typhi and Pseudomonas aeruginosa by DD and AWD methods respectively. However, aqueous leaf extract (ALE) and ethanolic leaf extract (ELE) and their combinations depicted appreciable antibacterial activity on the pathogens but incomparable to MLE. Generally, there was enhancement of bioactivties with the incorporation of Alum to the leaf extracts (irrespective of solvent of extraction) on a dose response fashion particularly by AWD method. Furthermore, the low MIC values of